Evaluating walkability through a multi-criteria decision analysis approach - Manzolli, Jônatas Augusto (2021)
Manzolli, J. A., Oliveira, A., & Neto, M. D. C. (2021). Evaluating walkability through a multi-criteria decision analysis approach: A lisbon case study. Sustainability (Switzerland), 13(3), 1-20. [1450]. https://doi.org/10.3390/su13031450